2018
DOI: 10.1002/2017ja024931
|View full text |Cite
|
Sign up to set email alerts
|

Neoclassical Diffusion of Radiation‐Belt Electrons Across Very Low L‐Shells

Abstract: In the presence of drift‐shell splitting intrinsic to the International Geomagnetic Reference Field magnetic field model, pitch angle scattering from Coulomb collisions experienced by radiation‐belt electrons in the upper atmosphere and ionosphere produces extra radial diffusion, a form of neoclassical diffusion. The strength of the neoclassical radial diffusion at L < 1.2 exceeds that expected there from radial‐diffusion mechanisms traditionally considered and decreases with increasing L‐shell. In this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…The <D αα > is several orders of magnitude higher near the South Atlantic Anomaly (SAA) (~longitude = 300°) and at smaller equatorial PAs (PA < 65°), since the altitude of electron's mirror point in these regions is much lower (as illustrated in Li et al, ). These <D αα > results are comparable to previous calculations based on different ionospheric plasma models (e.g., Selesnick, , that used the global core plasma model [Gallagher et al, ] and Cunningham et al, , that used the IRI 2007 model [Bilitza & Reinisch, ]). The bounce‐averaged energy loss rates of 304‐keV electrons at L = 1.25 calculated based on equation are shown in Figures g–i.…”
Section: Model Descriptionsupporting
confidence: 86%
See 3 more Smart Citations
“…The <D αα > is several orders of magnitude higher near the South Atlantic Anomaly (SAA) (~longitude = 300°) and at smaller equatorial PAs (PA < 65°), since the altitude of electron's mirror point in these regions is much lower (as illustrated in Li et al, ). These <D αα > results are comparable to previous calculations based on different ionospheric plasma models (e.g., Selesnick, , that used the global core plasma model [Gallagher et al, ] and Cunningham et al, , that used the IRI 2007 model [Bilitza & Reinisch, ]). The bounce‐averaged energy loss rates of 304‐keV electrons at L = 1.25 calculated based on equation are shown in Figures g–i.…”
Section: Model Descriptionsupporting
confidence: 86%
“…As in the work of Cunningham et al (), we use the NRLMSISE‐00 model (Picone et al, ) for the number densities of neutral H, He, N, N 2 , O, O 2 , and Ar as a function of altitude, latitude, and the F 10.7 index, and we sample the model output at each point along the magnetic field line at a given location, date, and time using a fixed value of F 10.7 = 70 and Ap = 4. For charged species, we use the H + , He + , O + , NO + , and O 2 + output of the IRI 2012 (Bilitza et al, ).…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…They specifically concluded that the model's underestimation when compared to data at high values was due to local acceleration from wave-particle interactions, which was not addressed by their model. In the same perspective, the VERB-3D (e.g., Kim et al, 2011;Shprits et al, 2009;Subbotin et al, 2010) code and the DREAM-3D code (e.g., Cunningham et al, 2018;Tu et al, 2013) are fed with PSD data derived from a variety of magnetic fields (preprocessing step), but they still account for a dipole field when the coordinate transformations are required through the resolution of the Fokker-Planck equation. Nevertheless, the absence of local acceleration in the 1D-RFP model is a strong limitation for storm times.…”
Section: Introductionmentioning
confidence: 99%